2013
DOI: 10.1080/22311866.2013.817749
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin Inhibits Growth, Morphogenesis and Biofilm Formation byCandida albicans

Abstract: Vanillin, a major component of the vanilla is known to exhibit various antimicrobial properties including inhibition of bacterial biofilms. However, a systematic study on activities of vanillin against the most common fungal pathogen, Candida albicans, is lacking. In this study, broth micro dilution method was used to assess vanillin's activity on the planktonic growth of C. albicans. Minimum inhibitory concentration (MIC) was established at 1 mg ml -1 of vanillin. Prevention of yeast to hyphae morphogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…For the S. epidermidis strain 745, syringic acid had a similar effect at all three concentrations. Similar results for vanillin were observed in Hafnia alvei [38], Pseudomonas aeruginosa [39], and Candida albicans [40], in which biofilm formation was inhibited up to 80%. Syringic acid anti-biofilm and anti-QS potential have not previously been analyzed.…”
Section: Discussionsupporting
confidence: 83%
“…For the S. epidermidis strain 745, syringic acid had a similar effect at all three concentrations. Similar results for vanillin were observed in Hafnia alvei [38], Pseudomonas aeruginosa [39], and Candida albicans [40], in which biofilm formation was inhibited up to 80%. Syringic acid anti-biofilm and anti-QS potential have not previously been analyzed.…”
Section: Discussionsupporting
confidence: 83%
“…Efficacy of essential oils and their components against drug resistant biofilms of C. albicans is of importance. These activities may be mediated through inhibition of membrane ergosterol and signalling pathways involved in yeast to hyphae morphogenesis (Agarwal et al, 2008;Raut et al, 2013bRaut et al, , 2013c. Essential oils also possess cell cycle inhibitory activities against C. albicans.…”
Section: Antifungal Activities Of Essential Oilsmentioning
confidence: 98%
“…Concentration-dependent decrease of cellular ergosterol in the presence of vanillin indicated that inhibition of ergosterol biosynthesis may be a probable target. [ 19 ] This was supported by our study wherein C. albicans exhibits a good zone of inhibition which is equivalent to that of ketoconazole.…”
Section: Discussionmentioning
confidence: 56%